2012
DOI: 10.1002/eji.201141852
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Tim‐3 signaling restores the virus‐specific CD8+T‐cell response in patients with chronic hepatitis B

Abstract: Chronic hepatitis B (CHB) is characterized by functionally impaired virus-specific CD8+ T-cell responses. However, the mechanism underlying this dysfunction has not been fully clarified. We examined the role of a newly identified protein, T-cell immunoglobulin domain and mucin domain-containing molecule-3 (Tim-3), in regulating the antiviral CD8 + T-cell response in CHB patients. Tim-3 expression on peripheral virus-specific

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
116
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(123 citation statements)
references
References 25 publications
(47 reference statements)
7
116
0
Order By: Relevance
“…Furthermore, Tim-3 silencing enhanced IFN-γ production and even indirectly affected HBV neutralizing antibody production, suggesting the potential role of Tim-3 in the host antiviral immune response against HBV infection [17] . Two years later, Wu et al [18] studied the relationship between Tim-3 expression on peripheral T cell subsets and disease progression in patients with chronic hepatitis B (CHB). They found that Tim-3 expression is increased on CD4 + and CD8 + T cells, and its expression is associated with the severity of CHB.…”
Section: Tim-3 and Effector T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Tim-3 silencing enhanced IFN-γ production and even indirectly affected HBV neutralizing antibody production, suggesting the potential role of Tim-3 in the host antiviral immune response against HBV infection [17] . Two years later, Wu et al [18] studied the relationship between Tim-3 expression on peripheral T cell subsets and disease progression in patients with chronic hepatitis B (CHB). They found that Tim-3 expression is increased on CD4 + and CD8 + T cells, and its expression is associated with the severity of CHB.…”
Section: Tim-3 and Effector T Cellsmentioning
confidence: 99%
“…After control of CHB infection, Tim-3 expression decreases. Moreover, the percentage of Tim-3 + T cells is negatively correlated with plasma IFN-γ and T-bet mRNA levels, indicating that high levels of Tim-3 expression inhibit T cell activity [18] . [20] .…”
Section: Tim-3 and Effector T Cellsmentioning
confidence: 99%
“…T cells in patients with chronic viral infections, including human immunodeficiency virus (HIV) [23], hepatitis B virus [24] and hepatitis C virus (HCV) [25]. Blockade of both TIM-3 and PD-1 pathways can restore T cell proliferation and effector potential, suggesting that both TIM-3 and PD-1 pathways play a major role in CD8…”
Section: Tim-3 In Normal Hematopoiesismentioning
confidence: 99%
“…Moreover, several reports have described the up-regulation of inhibitory receptor expression by HBV-specific CD8? T cells [5][6][7][8][9][10][11][12]. These studies suggest that HBV-specific CD8?…”
mentioning
confidence: 86%